Assessment of interdisciplinary communication for Category 1 caesarean sections. (October 2013) - Kasa, S. P. B.; Galimberti, A.; Wrench, I. J.
<x xml:space="preserve">Abstract</x> We assessed how often the urgency of Category 1 caesarean sections was incorrectly recorded by the anaesthetic and theatre teams. Category 1 caesarean sections were identified over a 15-month period (September 2010 to November 2011), from the daily audit of emergency caesarean sections undertaken by the obstetric team. The categories of urgency as recorded by the attending anaesthetist and theatre team were noted for each case. There were 236 Category 1 caesarean sections identified, of which 47 were incorrectly recorded as Category 2 by either the anaesthetist alone (34), the theatre team alone (1) or both (12). Where the category of urgency was correctly recorded, 11.6% of cases had a decision-to-delivery interval of more than 30 min compared with 27.7% of cases recorded as Category 2 (p = 0.01, Fisher's exact test).